Growth and regeneration of Cryptocoryne ciliata (Roxb.) Fisch. ex Wydler (Araceae) under ex-situ conditions - Alfasane, Md Almujaddade; Khondker, Moniruzzaman; Begum, ZN Tahmida (Bangladesh Journal of Botany, 2010)
Cultivation of Cryptocoryne ciliata (Roxb.) Fisch. ex Wydler via seeds resulted 80% survivality.The plant yearly produced 4-8 new leaves whose length varies from 45 to 52 cm and showed highest elongation in summer (1.04 ± 0.21 cm/day), medium (0.82 ± 0.15 cm/day) in monsoon. During winter and autumn foliar parts decompose. The highest growth was associated with 776.83 ± 107.21 μE m-2s-1 PAR, 31.58 ± 2.14°C water temperature and 12.74 ± 0.53 hr day length. The plants grew in brown to blackish-brown wet soils having pH, moisture content, OC, OM, CEC of the soil 6.95, 29%, 2.16%, 3.72% and 4.29 me/100 g soil, respectively. Available nitrogen, phosphorus, potassium and sulphur were 620, 3.09, 32 and 370 ppm, respectively. Key words: Cryptocoryne ciliata; Ex-situ culture; Growth; Regeneration DOI: 10.3329/bjb.v39i1.5536 Bangladesh J. Bot. 39(1): 115-118, 2010 (June)